EVALUATION OF THE EFFECTIVENESS OF GAPSEAL IN ELIMINATING MICRO-LEAKAGE AT THE IMPLANT-ABUTMENT INTERFACE - Shomurodov K.E.; Kurmaev S.I.; Mirkhusanova R.S. (Scholar Express Journals, 2025)
The study examined the effectiveness of the GapSeal in prevention of bacterial invasion through a micro gap in the implant-abutment joint by evaluating clinical parameters, as well as qualitative and quantitative assessment of the level of contamination of the internal components of dental implants. The results of clinical and microbiological studies confirmed the effectiveness of GapSeal, which resulted in minimal bacterial contamination and no signs of inflammation in the dental implant area.
Keywords: dental implants; bacterial invasion; microflow